Synthesis of Bio-Oil from Oil Palm’s Empty Fruit Bunch via Pyrolysis - Azizan, M Tazli; Yusup, Suzana; Laziz, F D Mohd; Ahmad, Murni M (2009)
Due to the increase in crude price oil prices and environmental concerns, a search for sustainable lternative fuel has gained significant attention. This involves the conversion of biomass to produce multiple type of fuels and products via pyrolysis or gasification. This work focused on synthesizing bio-oil from a type of oil palm waste, i.e. empty fruit bunch. The influences of variables such as temperature, sample size and reaction time on the amount of bio-oil produced as well as its composition were investigated. The pyrolysis process was carried out using Fixed Bed Activation Unit under nitrogen gas flow rate of approximately 0.1 ml/min after the sample has undergone a pretreatment process. The optimum condition for pyrolysis of empty fruit bunch was found to be at 500o C with particle size of 250μm and 3 hours of reaction time. Characterization of pyrolysis liquid produced in terms of density, pH, calorific value and the solid content was determined and reported